2020
DOI: 10.1093/icvts/ivaa022
|View full text |Cite
|
Sign up to set email alerts
|

Enteral immunonutrition versus enteral nutrition for patients undergoing oesophagectomy: a systematic review and meta-analysis

Abstract: OBJECTIVES According to retrospective studies, oesophageal carcinoma is the second deadliest gastrointestinal cancer after gastric cancer. Enteral immunonutrition (EIN) has been increasingly used to enhance host immunity and relieve the inflammatory response of patients undergoing oesophagectomy; however, conclusions across studies remain unclear. We aimed to evaluate the effect of EIN on the clinical and immunological outcomes of patients undergoing oesophagectomy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
9
0
2
Order By: Relevance
“…Correspondingly, perioperative immunonutrition was found to reduce postoperative morbidity in gastrointestinal cancer surgery in a systematic review of randomized controlled trials (RCTs) [37]. However, another recent metaanalysis of RCTs with a specific focus on esophagectomy did not confirm a positive effect of immunonutrition on AL, overall morbidity, postoperative hospital stay, or immune indices such as C-reactive protein, interleukin-6, IL-8, and tumor necrosis factor-α [38]. Therefore, immunonutrition prior to esophageal cancer surgery remains a controversial issue.…”
Section: Preoperative Nutritionmentioning
confidence: 99%
“…Correspondingly, perioperative immunonutrition was found to reduce postoperative morbidity in gastrointestinal cancer surgery in a systematic review of randomized controlled trials (RCTs) [37]. However, another recent metaanalysis of RCTs with a specific focus on esophagectomy did not confirm a positive effect of immunonutrition on AL, overall morbidity, postoperative hospital stay, or immune indices such as C-reactive protein, interleukin-6, IL-8, and tumor necrosis factor-α [38]. Therefore, immunonutrition prior to esophageal cancer surgery remains a controversial issue.…”
Section: Preoperative Nutritionmentioning
confidence: 99%
“…However, patients will experience a series of serious complications after surgery such as infection and anastomotic leakage due to immunosuppression and in ammatory response (8,10). Therefore, it is critically important to supply immune-modulating substances such as arginine and omega-3-fatty acids to SEN, which was de ned as EIN (7,17). Although the effectiveness of EIN in patients receiving gastrointestinal surgery has been established (8)(9)(10), the role of EIN in EC patients undergoing esophagectomy remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…To date, two meta-analyses (17,18) investigating the effectiveness of EIN for treating EC patients receiving esophagectomy have been published. Li and colleagues performed a meta-analysis of six articles to compare the effectiveness between EIN and SEN in patients receiving oesophagectomy, and found that impact of EIN on immunological status, biological status or clinical outcomes remains unclear (17). However, this nding must be cautiously interpreted because this meta-analysis missed four eligible studies (37,39,43,44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations